Juridical Analysis of Option Agreements in Apartment Ownership by Foreign Nationals - Meily Ferawati; Irpan Husein Lubis; Erniyanti Erniyanti; Markus Gunawan (Annals of Justice and Humanity, 2026)
Purpose: This study examines the legal protection of option agreements used by foreign nationals (FNs) to acquire apartment ownership in Batam City. It evaluates the regulatory framework, practical implementation, challenges, and the extent to which such agreements provide legal certainty for both developers and FNs. Methodology: A normative juridical approach was combined with a socio-legal method. Secondary data were obtained from legislation, legal literature, and jurisprudence, while primary data were gathered through interviews with notaries, government officials, developers, and foreign buyers in Batam. Results: The findings reveal that option agreements, though widely applied, lack explicit regulation in Indonesian law. Their legal force relies on the contractual freedom principle under the Civil Code, making them valid but weak in providing ownership rights. In practice, they are often used as alternatives to bypass restrictions on foreign ownership, but this creates potential legal uncertainty, especially in cases of default, regulatory changes, or disputes. Conclusion: Option agreements serve only as contractual instruments and fail to provide comprehensive legal protection or full ownership rights for FNs under Indonesian agrarian law. Clearer statutory provisions are required to enhance certainty and prevent abuse. Limitations: The research is limited to Batam City and does not fully capture variations across other regions. Data on disputes and enforcement are also limited. Contribution: This study identifies regulatory gaps in option agreements and emphasizes the need for government intervention through clearer policies, offering recommendations for policymakers, land agencies, and notaries to enhance investor protection, legal certainty, and national sovereignty.